2019
DOI: 10.1038/s41593-019-0406-3
|View full text |Cite
|
Sign up to set email alerts
|

High-order coordination of cortical spiking activity modulates perceptual accuracy

Abstract: The accurate relay of electrical signals within cortical networks is key to perception and cognitive function. Theoretically, it has long been proposed that temporal coordination of neuronal spiking activity controls signal transmission and behavior. However, whether and how temporally precise neuronal coordination in population activity influences perception is unknown. Here, we recorded from neuronal populations in early and mid-level visual cortex (areas V1 and V4) simultaneously to discover that the precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 52 publications
(78 reference statements)
2
48
0
Order By: Relevance
“…Studies have found that these fluctuations correlate with behavior, including pupil diameter [70,103,63,42,24,59,74,100], locomotion [27,81], attention [77,96,66,38], task difficulty [86] and learning [13,71]. In addition, these fluctuations may have a computational purpose, such as changing the structure of noise correlations to improve the fidelity of stimulus encoding [18,65,8,33], passing information from one brain area to another [85,87,88,95,89,93], or priming neurons to certain features of the stimulus [72,9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that these fluctuations correlate with behavior, including pupil diameter [70,103,63,42,24,59,74,100], locomotion [27,81], attention [77,96,66,38], task difficulty [86] and learning [13,71]. In addition, these fluctuations may have a computational purpose, such as changing the structure of noise correlations to improve the fidelity of stimulus encoding [18,65,8,33], passing information from one brain area to another [85,87,88,95,89,93], or priming neurons to certain features of the stimulus [72,9].…”
Section: Discussionmentioning
confidence: 99%
“…390 The necessity of higher-order patterns for stable activity has strong implications for 391 neural coding. Previous work has already demonstrated that correlations enhance 392 coding, with triplet correlations having an advantage over pairwise 393 [5,16,18,[21][22][23][52][53][54]. The neural code must rest upon a foundation of stable 394 propagation of spikes, which we have shown in turn rests on higher-order motifs and 395 coordinated integration.…”
mentioning
confidence: 77%
“…The term 'motif' refers to a pattern formed by a group of units in a network. Previously 170 we found that triplet motifs were informative of synaptic integration [19] and also 171 increased the power of encoding models [18,[21][22][23]. Here we focused our analysis on 172 similar patterns of connectivity in the recruitment network, involving groups of three 173 units [43].…”
mentioning
confidence: 98%
“…Unlike attention-related changes in pre-target spike rates, the present results demonstrate that local and between-region patterns of pre-target spike-LFP phase coupling are predictive of behavioral outcomes. Spike-LFP phase coupling is an indication of spike-timing control and represents a possible mechanism for temporally organizing neural activity to optimize (i) local computations and (ii) the transfer of information between brain regions Lisman and Idiart, 1995;Shahidi et al, 2019;Siegel et al, 2009;Voloh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%